Pengaruh penambahan limbah cangkang kelapa sawit terhadap nilai kuat tekan beton - Randi Bastika; Yoseph Yustinus; Nur Aida (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
Ketapang regency is one of the oil palm producing districts in West Kalimantan. The area of oil palm plantations is 650,110 Ha with 2,509,110 tons of oil palm plantations produced in 2022. Under these conditions, will produce quite large amounts of palm oil shell waste. This waste can be used as a mixture of materials for making concrete. Waste utilization is one solution that can be done to maintain existing natural resources. The aim of this research is to determine the effect of adding variations in palm oil shell waste of 5%, 10%, and 15% on the compressive strength of concrete. This research is experimental research in the structure and materials laboratory, Departement of Civil Engineering, Ketapang State Polytechnic. The research was carried out from 12 August 2023 to 17 September 2023. The average value of concrete compressive strength at 28 days for normal concrete and the 5% palm oil shell variation is included in the standard K-200 concrete quality value, but there is a decrease in the 10% and 15% palm oil shell variations. This result is supported by the SPSS test results of two mean tests between 0% and 5% which are the same, there is no difference, but for other variations it is different. The greater the use of palm oil shells in the concrete mixture will reduce the compressive strength value of the concrete. Variation of palm shell mixture that produces the maximum compressive strength of concrete at a variation of 5% with an average value of 221.01 kg/cm2.